Traumatic brain injury: molecular biomarkers, genetics, secondary consequences, and medical management - Lipsky, Robert H.; Witkin, Jeffrey M.; Shafique, Hana; Smith, Jodi L.; Cerne, Rok; Marini, Ann M. (Frontiers in Neuroscience, 2024)
Traumatic brain injury (TBI) has reached epidemic proportions worldwide. The consequences of TBI can be severe even with repetitive mild trauma. If death and coma are avoided, the consequences of TBI in the long term typically involve dizziness, sleep disturbances, headache, seizures, cognitive impairment, focal deficits, depression, and anxiety. The severity of brain injury is a significant predictor of outcome. However, the heterogenous nature of the injury makes prognosis difficult. The present review of the literature focuses on the genetics of TBI including genome wide (GWAS) data and candidate gene associations, among them brain-derived neurotrophic factor (BDNF) with TBI and development of post-traumatic epilepsy (PTE). Molecular biomarkers of TBI are also discussed with a focus on proteins and the inflammatory protein IL1-β. The secondary medical sequela to TBI of cognitive impairment, PTE, headache and risk for neurodegenerative disorders is also discussed. This overview of TBI concludes with a review and discussion of the medical management of TBI and the medicines used for and being developed at the preclinical and clinical stages for the treatment of TBI and its host of life-debilitating symptoms.